Feeding habits of cyprinidae in Batang Kerang floodplain, Balai Ringin, Serian, Sarawak - Maclin, anak Masek (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Diet analysis is important for the studies of competition, predator-prey relationship, trophic level, food webs and potential fish aquaculture. The objectives of this study are to identify the feeding habit of Cyprinidae and to analyze the food composition and frequency of occurrence of food items in the fish gut in Batang Kerang habitat. Fish samples were collected from Batang Kerang floodplain, Balai Ringin in December 10th to 11th, 2011 and in April 13th to 14th, 2012 to examine the gut content. One hundred and fifty specimens were used for the study. The feeding habits were determined based on Gut Relative Index (GRI), food composition and frequency of occurrence. The results showed that the major food item consumed by Cyprinidae species are plant matter (47.02%) followed by detritus (43.86%) and insects (3.86%). Most of the species were herbivorous, followed by omnivorous and carnivorous. Further study on detail feeding habit of fish should be done.